Peran Pemberdayaan Perempuan Dalam Meningkatkan Ketahanan Ekonomi Keluarga Di Desa Sugihwaras Barat - Rati Rati; Ines Tasya Jadidah; Sita Lutfiastuti Hasanah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Women’s empowerment is one of the key strategies for strengthening family economic resilience, particularly in rural areas. Women play dual roles, not only as managers of household affairs but also as economic actors who contribute to family income. This article aims to provide a general review of the role of women’s empowerment in enhancing family economic resilience in Sugihwaras Barat Village. The approach used is descriptive qualitative, examining various forms of women’s empowerment activities such as micro-enterprises, productive skills development, and participation in community-based economic groups. The findings indicate that women’s empowerment can increase family income, strengthen economic independence, and help families cope with economic pressures. Therefore, women’s empowerment plays a strategic role in creating family economic resilience in Sugihwaras Barat Village.